2017
DOI: 10.1177/2374289517707506
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Intervention for Reduction of Redundant Testing

Abstract: Laboratory data are critical to analyzing and improving clinical quality. In the setting of residual use of creatine kinase M and B isoenzyme testing for myocardial infarction, we assessed disease outcomes of discordant creatine kinase M and B isoenzyme +/troponin I (−) test pairs in order to address anticipated clinician concerns about potential loss of case-finding sensitivity following proposed discontinuation of routine creatine kinase and creatine kinase M and B isoenzyme testing. Time-sequenced intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Similarly, CK‐MB was once over‐utilised in the Emergency Department and has now become an obsolete test, no longer recommended by the current literature and practices . In a study at a large academic medical centre evaluating the clinical and financial implications of creatine kinase‐muscle/brain (CK‐MB) in the ED, it was shown that CK‐MB can be safely removed from ordering practices without affecting patient outcome and with cost savings of approximately $47 000 per year . Zhang et al estimated the financial impact of reduction in CK‐MB at a community hospital to be around $463 744 effectively decreasing the unnecessary lab tests for acute coronary syndrome with significant cost savings to the healthcare system .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CK‐MB was once over‐utilised in the Emergency Department and has now become an obsolete test, no longer recommended by the current literature and practices . In a study at a large academic medical centre evaluating the clinical and financial implications of creatine kinase‐muscle/brain (CK‐MB) in the ED, it was shown that CK‐MB can be safely removed from ordering practices without affecting patient outcome and with cost savings of approximately $47 000 per year . Zhang et al estimated the financial impact of reduction in CK‐MB at a community hospital to be around $463 744 effectively decreasing the unnecessary lab tests for acute coronary syndrome with significant cost savings to the healthcare system .…”
Section: Discussionmentioning
confidence: 99%
“…There are significant emotional costs of fear, anxiety, and concern to patients, families, and friends during periods of diagnostic and therapeutic uncertainty, as well as significant health risks for the patient when invasive procedures such as cardiac catheterization are involved. 18…”
Section: Utilization Managementmentioning
confidence: 99%
“…18,19 Data about the ordering practices linked to actual outcomes can address the optimism bias inherent in human nature that “more is better” and that unconventional reasons for intervention will improve care. 18,19…”
Section: Utilization Managementmentioning
confidence: 99%
See 2 more Smart Citations